Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10903-011-9496-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Immigrant Health Professionals into the US Health Care Workforce: A Report from the Field

Abstract: Since 2001, the Welcome Back Initiative (WBI) has implemented a program model in ten US cities to help foreign trained health professionals enter the US healthcare workforce. This paper reviews how the WBI has worked toward achieving this goal through community needs assessment, the development of a comprehensive program model and ongoing program evaluation. Since 2001, the WBI has served over 10,700 immigrant health professionals. Of these participants, 66% were not previously working in the health sector. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…The first category refers to programmes combining teaching and clinical practise (n = 11 [15, 18–21, 41, 42, 46, 51, 52, 54]). The second category refers to programmes only offering teaching (n = 10 [22, 2527, 39, 43, 44, 47, 50, 55]) or practise (n = 2 [40, 48]), whereas programmes in the third category (n = 8 [14, 23, 24, 37, 38, 45, 49, 53]) offered primarily elements of social support, such as mentorship [23, 37], peer support [45], reflection through exchange with local staff [14], case management and counselling [38], career advice [45], social support or group activities. Within the third category, two programmes relied on media-based teaching only via videoconferences or web-tools (n = 2 [24, 49]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first category refers to programmes combining teaching and clinical practise (n = 11 [15, 18–21, 41, 42, 46, 51, 52, 54]). The second category refers to programmes only offering teaching (n = 10 [22, 2527, 39, 43, 44, 47, 50, 55]) or practise (n = 2 [40, 48]), whereas programmes in the third category (n = 8 [14, 23, 24, 37, 38, 45, 49, 53]) offered primarily elements of social support, such as mentorship [23, 37], peer support [45], reflection through exchange with local staff [14], case management and counselling [38], career advice [45], social support or group activities. Within the third category, two programmes relied on media-based teaching only via videoconferences or web-tools (n = 2 [24, 49]).…”
Section: Resultsmentioning
confidence: 99%
“…Within the third category, two programmes relied on media-based teaching only via videoconferences or web-tools (n = 2 [24, 49]). However, in most cases (n = 4 [23, 38, 45, 53]) these social support elements were combined with teaching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attrition is even greater for internationally educated nurses who are much more likely to be working outside the nursing profession. For instance, in the USA, Fernandez‐Pena () found that 66% of internationally educated health professionals were not working in the healthcare sector. Furthermore, most of those who were working in the health sector were not working in roles that commensurate with their education and experience.…”
Section: Discussionmentioning
confidence: 99%
“…The WBI is a network of 10 centers in 9 states providing orientation, counseling, and support to foreign-trained health workers. 9 Another nonprofit program, Upwardly Global (UpGlo), helps work-authorized skilled immigrants DOI: http://dx.doi.org/10.4300/JGME-D-18-01010…”
Section: National Regional and State-level Initiativesmentioning
confidence: 99%